Die Pendulum-effek tussen ortodoksie en vernuwing in die Suid-Afrikaanse Kerkgeskiedenis met spesiale verwysing na die tydperk 1850 tot 1950 - Fourie, C. K. (Verbum et ecclesia, 2000)
The pendulum effect between orthodoxy and renewal in South African Church History with special reference to 1850-1950 Since the beginning of Church History, a typical phenomenon has occurred, in which certain extremist movements were formed in reaction to each other. This has led to a pendulum effect between the two extremes - one, where the emphasis falls on the emotions, and the other, which carries a more intellectual character.